The relationship between ethnicity and place of birth in England: a mixed-methods study - Frances Rivers; Christopher Grollman; Zahra Khan; Marina A. S. Daniele (BMC, 2024)
Abstract Background UK maternity policy advocates a choice of birthplace in an obstetric-led unit (OU), a midwife-led unit (MLU) or at home. Although robust evidence supports the safety of birth in midwife-led settings, particularly for women with uncomplicated pregnancies, most births are in the OU. Women and babies from ethnic minority communities experience major health disparities and inequitable care, but there is limited research examining birthplace choices through an ethnicity lens. This study investigated the association between ethnicity and place of birth at an urban NHS Trust in England. Methods A mixed-methods sequential explanatory study. Analysis of births from 2014-2023 at a London NHS Trust included multivariable logistic regression analysis of birthplace by ethnicity. Planned or pre-labour Caesareans, pre-term, and multiple births were excluded. Significant disparities between White and South Asian women were identified which informed the focus of the qualitative study. Semi-structured interviews with 10 women of South Asian heritage who had given birth in the OU, the alongside MLU or at home were conducted and analysed thematically. Results More White women gave birth in midwife-led settings (27.5%) than all other ethnicities, particularly South Asian women (20.6%). South Asian women had fewer homebirths (0.8%) than White women (2.7%) and were much less likely to birth in a midwife-led setting after adjusting for parity, maternal age, BMI, previous Caesarean, presence of diabetes or hypertensive disorders and onset of labour (aOR 0.61, 95% CI 0.51-0.73, p < 0.001). Places of birth were similar for Black and White women, although the number of Black women in the population was too low to detect significant differences. Themes generated from interviews included the assumption that birth is hospital-based and doctor-led; choosing a midwife-led birth setting went against the cultural norm, but felt safe - physically, psychologically and culturally. Conclusions There are ethnic disparities in place of birth. Cultural factors seem influential, but barriers to choice, such as limited evidence-sharing by midwives, may disproportionately affect women from ethnic minority communities, who may particularly benefit from midwife-led birth settings. Women need personalised information about options. Improving choice of birthplace is a step towards reducing health inequalities and promoting optimal health.